The effects of propylene glycol addition in the combination of calcium hydroxide and propolis on compressive and flexural strength - Mandojo Rukmo; Nirawati Pribadi; Elisa Kusuma Wardani; Sukaton; Belinda Belinda Meilani Perdana Putri (Universitas Airlangga, 2022)
Background: The mechanical properties of pulp-capping materials may affect their resistance to fracture during placement of a final restorative material or while supporting an overlying restoration over time when the mastication process is carried out. The combination of calcium hydroxide and propolis as a pulp capping material has the weakness on mechanical properties so it is necessary to add another material to improve its mechanical properties. Propylene glycol is used as a vehicle because it improves its handling property. Purpose: To explain how the compressive and flexural strength of the pulp capping material in the combination of calcium hydroxide, propolis, and propylene glycol compared without adding of propylene glycol. Methods: The study used 4 treatment groups with each group consisting of 7 replications. Control group is a combination of calcium hydroxide-propolis with a ratio of 1: 1.5, group 1 is a combination of calcium hydroxide-propolis-propylene glycol 20% with a ratio of 1:1.5:0.375, group 2 is a combination of calcium hydroxide-propolis-propylene glycol 30% with a ratio of 1:1.5:0.375, and group 3 is a combination of calcium hydroxide-propolis-propylene glycol 30% with a ratio of 1:1.5:0.375. Materials were mixed according to comparison and printed on a cylindrical mold with the size of 4 mm x 6 mm and a block mold with the size 65 mmx10 mmx6 mm. Then, the compressive and flexural strength was tested using an Autograph test instrument. Results: The statistical analysis was performed with ANOVA and Tukey HSD’s post-hoc test. There were statistically significant differences on compressive and flexural strength between groups (P<0.05). Conclusion: Addition of propylene glycol in the combination of calcium hydroxide and propolis have an influence of increasing of compressive and flexural strength, especially in the addition of 40% propylene glycol.